2024
DOI: 10.3390/gels10040226
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Gamma Radiation on Different Gelatin Nanofibers and Gelatins

Carmen Gaidau,
Maria Râpă,
Gabriela Ionita
et al.

Abstract: Gelatin nanofibers are known as wound-healing biomaterials due to their high biocompatible, biodegradable, and non-antigenic properties compared to synthetic-polymer-fabricated nanofibers. The influence of gamma radiation doses on the structure of gelatin nanofiber dressings compared to gelatin of their origin is little known, although it is very important for the production of stable bioactive products. Different-origin gelatins were extracted from bovine and donkey hides, rabbit skins, and fish scales and us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…However, the fabricated bioactive nanofibers showed an average diameter very similar to the diameter of ECM collagen fibers found in the skin, typically ranging from 50 nm to 500 nm. In an extensive study examining the average diameter of gelatin nanofibers prepared by electrospinning gelatins derived from different sources—bovine, donkey, rabbit, and fish scale—it was observed that the donkey gelatin exhibited the smallest nanofiber diameter (73.15 nm ± 3.37 nm) [ 34 ]. The authors concluded that the origin of gelatin and optimized electrospinning conditions are essential for achieving nanofibers with dimensions closely resembling those of the extracellular matrix (ECM).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the fabricated bioactive nanofibers showed an average diameter very similar to the diameter of ECM collagen fibers found in the skin, typically ranging from 50 nm to 500 nm. In an extensive study examining the average diameter of gelatin nanofibers prepared by electrospinning gelatins derived from different sources—bovine, donkey, rabbit, and fish scale—it was observed that the donkey gelatin exhibited the smallest nanofiber diameter (73.15 nm ± 3.37 nm) [ 34 ]. The authors concluded that the origin of gelatin and optimized electrospinning conditions are essential for achieving nanofibers with dimensions closely resembling those of the extracellular matrix (ECM).…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, there is evidence that the use of inflammable liquids with high shear strength and voltage can potentially generate permanent denaturation of the collagen fibrous structure [ 28 ]. Our previous publications reported the fabrication of nanofibrous wound dressings by the electrospinning process of different protein extracts, such as collagen derived from cattle hides [ 29 , 30 ], rabbit skins [ 31 , 32 ], fish scales [ 33 , 34 ], donkey hides [ 34 ], or keratin extracted from sheep wool [ 35 ], loaded with various non-active antimicrobial agents and having advanced regenerative properties for acute and chronic wound healing.…”
Section: Introductionmentioning
confidence: 99%